Mucosal vaccination with outer membrane vesicles derived from Bordetella pertussis reduces nasal bacterial colonization after experimental infection - Rudi, E.; Gaillard, E.; Bottero, D.; Ebensen, T.; Guzman, C. A.; Hozbor, Daniela (Frontiers in Immunology, 2024)
IntroductionWe previously identified Bordetella pertussis-derived outer membrane vesicles (OMVs) as a promising immunogen for improving pertussis vaccines. In this study, we evaluated the efficacy of our vaccine prototype in immunization strategies aimed at reducing disease transmission by targeting colonization in the upper airways while maintaining protection against severe disease by reducing colonization in the lower respiratory tract.MethodsWe assessed different mucosal administration strategies in a murine model, including homologous mucosal 2-dose prime-boost schedules and heterologous prime-boost strategies combining intramuscular (IM) systemic immunization with mucosal routes (intranasal, IN; or sublingual, SL). We utilized alum and c-di-AMP as adjuvants for the systemic and mucosal formulations of the OMV vaccine prototype, respectively. A homologous prime/boost IM immunization schedule and commercial vaccines were used for comparisons.ResultsAll tested heterologous schemes induced higher levels of specific IgG with significant avidity, as well as higher levels of IgG1 and IgG2c, compared to the corresponding homologous prime-boost 2-dose schemes via mucosal routes (OMVIN-IN or OMVSL-SL). High IgA levels were observed post-B. pertussis challenge following OMVIN-IN treatments and heterologous treatments where the second dose was administered via a mucosal route (prime-pull scheme). Furthermore, schemes involving the intranasal route, whether in a homologous or heterologous scheme, induced the highest levels of IL-17 and IFN-γ. Accordingly, these schemes showed superior efficacy against nasal colonization than the commercial vaccines. Homologous intranasal immunization exhibited the highest protective capacity against nasal colonization while maintaining an excellent level of protection in the lower respiratory tract. To further enhance protection against nasal colonization, we performed a comparative analysis of formulations containing either single or combined adjuvants, administered via homologous intranasal route. These assays revealed that the use of alum combined with c-di-AMP, did not enhance the immune protective capacity in comparison with that observed for the formulation containing c-di-AMP alone.ConclusionsAll the experiments presented here demonstrate that the use of OMVs, regardless of the scheme applied (except for OMVSL-SL), significantly outperformed acellular pertussis (aP) vaccines, achieving a higher reduction in bacterial colonization in the upper respiratory tract (p<0.01).